2011
DOI: 10.1021/ja110545h
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclic β-Sheet Peptides That Inhibit the Aggregation of a Tau-Protein-Derived Hexapeptide

Abstract: This paper describes studies of a series of macrocyclic β-sheet peptides 1 that inhibit the aggregation of a tau-protein-derived peptide. The macrocyclic β-sheet peptides comprise a pentapeptide “upper” strand, two δ-linked ornithine turn units, and a “lower” strand comprising two additional residues and the β-sheet peptidomimetic template “Hao”. The tau-derived peptide Ac-VQIVYK-NH2 (AcPHF6) aggregates in solution through β-sheet interactions to form straight and twisted filaments similar to those formed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
142
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(149 citation statements)
references
References 73 publications
5
142
0
2
Order By: Relevance
“…To verify this conclusion, we performed two control experiments. First we confirmed that the altered kinetics are due to disruption of the intermediate rather than the fibril β-sheets by adding Mac [31][32][33][34][35][36][37] . It seeds I26P fibril formation as it does with wild-type hIAPP, thus proving I26P can readily form fibrils and the proline mutation is not simply incompatible with the fibril structure.…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…To verify this conclusion, we performed two control experiments. First we confirmed that the altered kinetics are due to disruption of the intermediate rather than the fibril β-sheets by adding Mac [31][32][33][34][35][36][37] . It seeds I26P fibril formation as it does with wild-type hIAPP, thus proving I26P can readily form fibrils and the proline mutation is not simply incompatible with the fibril structure.…”
Section: Resultssupporting
confidence: 55%
“…Thus, the heptapeptide strand of the macrocycle is designed to bind to amyloid β-sheets with a matching sequence, whereas the other strand prevents further elongation. Similar macrocycles have been used previously to study the aggregation of a τ-derived hexapeptide, amyloid-β, β2-microglobulin, and truncated α-synuclein (33,34).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The VQIVYK peptide, termed PHF6, is a highly aggregative short segment located in the third repeat of the MT-binding region of the tau protein [17,18], which can assume the β-sheet structures necessary for the aggregation of tau into oligomers and NFTs [17,19]. This peptide is widely used as a model for studying tau aggregation and examining candidate inhibitors [20,21,22,23,24,25,26]. …”
Section: Introductionmentioning
confidence: 99%